Spatial Analysis and Risk Assessment of Heavy Metal in Aquaculture Sediment of Porong River Estuary - Eny Susilowati; Arief Rahmansyah; Sudarto Sudarto (Indonesian Journal of Environment and Sustainable Development, 2017)
Study on heavy metal contaminants in sediments provide major role because they have longer residence time. Increased levels of heavy metals in water which originally required for various metabolic processes may turn out to be toxic to aquatic organisms. The metal will be absorbed in the sediment then accumulated into microorganisms through the food chain. The purpose of this study is to analyze the spatial concentration of heavy metals in aquaculture’s sediments of in Porong River estuary. Firstly, this research was conducted by examined content of eight heavy metals in the sediment, then tested with ICP-MS instruments. Then, the calculation of some parameters was analyzed spatially with ArcGIS. IgeO Parameter of aquaculture sediment of Porong River Estuary from largest to smallest is are Hg> Pb> Cd> Mn> As> Cu> Zn> Co. EF value of aquaculture sediment of Porong river estuary from largest to smallest values are Hg> Pb> Cd> Mn> Cu> As> Zn> Co. DC Results obtained in all 12 stations of this study has value between is 27.47- 36.35 within the categorization Very High Degree of Contamination. ERI value shows that almost entirely area of Porong river estuary shows High Risk result.Keywords: Aquaculture, Heavy metal contamination, Porong river estuary, Sediment, Spatial